LIMA1 inhibits cisplatin resistance and malignant biological behavior of bladder cancer cells by suppressing the Wnt/β-catenin pathway - Zhong Lv; Shuchen Zhao; Haoran Wu (BMC Medical Genomics)
Abstract Objective This study aimed to explore the effect of LIM domain and actin binding 1 (LIMA1) on bladder cancer (BCa) cells and to investigate its underlying molecular mechanisms. Methods The expression of LIMA1 gene in clinical BCa tissue samples and BCa cell models was detected using real-time quantitative PCR and western blot. Subsequently, LIMA1 knockdown experiments were performed exclusively in the BCa J82 cell line, while LIMA1 overexpression was conducted only in the cisplatin-resistant J82/CR cell line. The proliferation of the cells was assessed by colony formation assay. Cisplatin resistance was evaluated by MTT assay. Migration and invasion of the cells were tested by Transwell assay. Additionally, the levels of key proteins in the Wnt/β-catenin signaling pathway were examined by western blotting. Results We found that LIMA1 was underexpressed in BCa tissues and cells (P < 0.01). Overexpression of LIMA1 inhibited the proliferation, migration, invasion, and epithelial-mesenchymal transition of BCa cells (P < 0.01) and improved their cisplatin resistance (P < 0.01), whereas knocking down LIMA1 produced opposite results (P < 0.01). Furthermore, overexpression of LIMA1 could suppress the Wnt/β-catenin signaling pathway in BCa cells (P < 0.01), and activation of this pathway partially reversed the anti-tumor effects produced by overexpression of LIMA1 (P < 0.01). Conclusion LIMA1 could inhibit the malignant biological behavior of BCa cells and weaken their cisplatin resistance by negatively regulating the Wnt/β-catenin signaling pathway. Our findings provide new insights for the clinical treatment of BCa.